Legal Politics in the 2024 Election Era in Indonesia - Saputra, Ade Rizki; Gunati, Mira; Miliyandra, Miliyandra; Firsanti, Ery Rachma; Haryono, Tri Agus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates legal politics in the 2024 election era in Indonesia with a focus on changes in regulations and decisions of judicial institutions that affect integrity, transparency and fairness in the general election process. By analyzing the development of legal politics during the election, this research aims to understand its impact on the foundations of democracy in Indonesia. The research methods used include document analysis, case studies, and interviews with relevant stakeholders. The results of the study highlight the important role of Constitutional Court decisions in shaping electoral legal politics, as well as the challenges and opportunities in realizing honest, fair and transparent general elections in the future